Calcium hydroxide as a clinical paradigm is surpassed by mineral trioxide aggregate (MTA) - Yepes-Delgado, Fanny Lucía; Castrillón-Yepes, César Augusto (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: as a result of scientific research, calcium hydroxide (CH) enjoyed a privileged position for several decades as a choice with high predictive abilities for pulp therapy. We are now witnessing the collapse of this paradigm due to the emergence of mineral trioxide aggregate (MTA) with its biocompatibility—an ability to stimulate mineralization—, antimicrobial properties, and other advantages that make it more successful in endodontic therapy. The objective of this topic review was to identify the uses of CH and MTA from 1995 to the present, in different clinical conditions. Methods: this review consisted of a comprehensive literature search in Medline, PubMed, and SciELO from 1995 to the present. It included titles, abstracts, full articles, systematic reviews, and meta-analysis related to CH and MTA. Results: a number of scientific studies highlight the properties of CH in pulp therapy; however, MTA has also been used and studied as a replacement material. Conclusions: according to research on this field, MTA can be used in the same situations for which CH is recommended, with better probabilities of success.